Upaya Persuasif Preventif dan Represif pada Kasus Pelarian oleh Warga Binaan Pemasyarakatan di Lembaga Pemasyarakatan Kelas 1 Surabaya: Preventive and Repressive Persuasive Efforts in Cases of Escape by Prisoners at Class 1 Surabaya Penitentiary - Pijar Bagus Prajnalaga; Samuji Samuji; Yeni Vitrianingsih (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2025)
A prisoner is a person who is punished for committing a crime. Meanwhile, according to the main dictionary of scientific terms, the meaning of a prisoner is a person in prison. The purpose of this study was to determine the security measures that can be applied to prevent and handle prisoner escape attempts at Class 1 Surabaya Penitentiary. This research method uses empirical legal research, with data collection through observation and interviews. The data found was analyzed using an empirical approach, conducting direct observations of inmates, talking to policy makers at the Penitentiary and found that there were three efforts, namely, persuasive, preventive, and repressive. The results of the study indicate that security and order are absolute in the security system at the Penitentiary. Security disturbances are the impact of the less than optimal persuasive and preventive efforts in the security system. Through persuasive efforts carried out by fulfilling rights and obligations, as well as fostering inmates in the form of skills and piety, these efforts have been running effectively and efficiently in preventing escapes. Preventive efforts by implementing security procedures for inmates, but these efforts have not been running effectively, because there are still shortcomings in terms of the number of personnel. Repressive efforts as a reaction to an incident, in the event of an attempted escape, coordination will be carried out with related parties and sanctions will be applied to inmates. This effort can be said to be an effort to take action and has been running effectively and providing legal protection to inmates. In the end, the government must pay more attention to the correctional system in Indonesia, because as a policy maker, the government has an important role in the progress of the correctional system in order to realize social justice for all Indonesian people.